PENGARUH STRATEGI PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN SKINCARE SARIAYU MARTHA TILAAR - Tesalonika Almatera Natalia Tampubolon (2022)
The purpose of this study is to prove that there is an effect of product, price, location, and promotion on purchasing decisions. This study uses a quantitative approach. Sources of data in this study using primary data. Respondents in this study were consumers who were using or had purchased Sariayu Martha Tilaar skincare products as many as 100 people located in the cities of Bekasi, Depok, Tangerang, Jakarta, and Bogor. Sampling was carried out using a non-probability sampling technique with purposive sampling. Data were collected using a questionnaire. The data analysis technique was carried out using descriptive analysis and also inferential analysis. Through data processing that has been carried out using SmartPLS3.0 the results are (1) the product has an effect on purchasing decisions with an original sample value of 73,2%, (2) price affects purchasing decisions with an original sample value of -19,9%, (3) location affects the decision purchase with the original sample value is 44,8%, and (4) Promotion has an effect on purchasing decisions with the original sample value is 4%. The result of the adjusted R-Square of purchasing decisions is 92,9%, indicating that the research model is very good in interpreting location, promotion, price, and the product together have a contribution to purchasing decisions on Sariayu Martha Tilaar skincare products.